Evaluasi Penerapan Green City Pada Taman Kota (Studi Kasus : Taman Kota Lumintang Denpasar) - Mahendra, I Gede Indra; Dwijendra, Ngakan Ketut Acwin (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2022)
The sustainability of urban environmental development can be realized with the concept of a Green City or Green City. The application of Green City can be applied by structuring a city's green open space. The existence of green open space in Denpasar City has made the Denpasar City government begin to restore the Lumintang City Park as a solution to urban problems that arise. The government participates in the arrangement of Lumintang City Park so that it can be directed to become a Green City element that focuses more on evaluating green open space, green community, and green energy. The purpose of this study is to evaluate whether Denpasar City Park Lumintang has implemented the Green City aspect or not and the changes to Lumintang City Park will be directed towards which direction to address the growth of Denpasar City in the future. The method used is qualitative with a descriptive approach. Data was collected through interviews and observations regarding the evaluation of green open space, green community, and green energy. The results show that based on the application of green city to the three parameters used, the implementation of green open space and green community has been implemented but in its application, it has not been optimal while green energy has not been implemented at all. So it is necessary to have the attitude of the government and the community in the development of this grand city.